Unterstützung der Handlungssicherheit von Pflegefachpersonen im Umgang mit Notfallsituationen in Pflegeheimen: Ergebnisse einer qualitativ-empirischen Studie - Rubeis, Giovanni; Hasseler, Martina; Primc, Nadia (Zeitschrift für Gerontologie und Geriatrie, 2023)
A significant number of emergency responses and hospitalizations of nursing home residents are considered avoidable and result in an unnecessary burden or health risk for residents. One cause of these unnecessary emergency responses lies in the lack of confidence of nursing personnel in their own actions and decisions. The goal of the NOVELLE project is to develop recommendations for action for certain emergency situations that enable nursing personnel to make operationalized decisions and empower them to take confident action. The challenges for nursing professionals to act with confidence in emergency situations were collated and assessed through a qualitative interview study. The results of this study are presented.